Public libraries and encouragement of reading and reading competencies of all citizens - Sabina Fras Popović; Polona Vilar; Petra Javrh (Vjesnik Bibliotekara Hrvatske)
Purpose: The paper links the fields of adult reading literacy and the role of Slovenian public libraries in promoting reading and strengthening reading competencies of adults. It reviews the relevant literature and, on this basis, develops theoretical reflections on the basic laws of adult reading competency development, the tasks of the public library service in the context of public libraries and the link between the two areas in order to present the potential of Slovenian public libraries in raising adult reading competency. The aim is also to provide an overview of the contemporary Slovenian literature in the field of public libraries and adult education. Methodology/approach. We used the content analysis method to analyze literature in two content segments: 1) Reading incentives in adulthood and the societal importance of adult reading ability. 2) The role of public libraries in enhancing adult reading ability. The sample included two segments of literature: 1) professional and scientific publications, mainly in the Slovenian area or by Slovenian authors, regardless of their year of publication (114 works) and 2) more recent publications (in 2016-23) in the journals Knjižnica and Organizacija znanja, which are the only Slovenian scientific and professional journals in the field of librarianship and related fields (219 works), a total of 333 publications. Results. We found that strengthening adults' reading competencies is part of the public library's mission in the local area, as the literature reviewed highlights this link. However, among the articles published between 2017 and 2023 in the two selected journals, we did not find any that would address this link or otherwise linked adult reading outcomes and the role of the public library in strengthening adult reading skills. Originality/applicability of the research: The results show that there are theoretical premises that link the fulfilment of the mission of Slovenian public libraries to the strengthening of adults' reading competencies, with an emphasis on those adults whose reading competencies have not been developed in a form that would enable them to integrate smoothly into modern society. Taking into account the theoretical foundations and using the results of international research, the possibilities for public libraries to strengthen their position as promoters not only of reading in general, but also as implementers of programmes to strengthen the reading competencies of adults who do not have these competencies in the strongest possible form, are suggested. However, this requires the application of these foundations to professional library work, and it is therefore necessary to strengthen the pro-activity of libraries in this area. Limitations of the study: the limitations of the study are related to the relevance of the data from the PIAAC 2016 international survey and the national survey on reading and shopping habits of adults in Slovenia. The latest data from the PIAAC international survey will not be available until 2028, while the latest results from the national survey will be published as early as 2024.